K.H Ahmad Dahlan's Contribution to the World of Da'wah and Education - Rizky A Tumangger (Getpress Management Journals, 2023)
K.H Ahmad Dahlan is a scholar who is known to be persistent in fighting for Islamic teachings in a rational and modern way. This article aims to find out the da'wah strategy used by K.H Ahmad Dahlan in the field of Islamic education and explain the methods of Islamic education according to K.H Ahmad Dahlan, as well as explain the relevance of K.H Ahmad Dahlan's da'wah strategy in increasing understanding of Islamic education. The method used in this research is the literature study method. The library study method is to display scientific reasoning arguments that explain the results of literature studies, the results of researchers' thinking regarding a problem or study topic. As a result of this research, the researcher concluded that the steps that K.H Ahmad Dahlan took in carrying out his da'wah mission used several strategies, including building self-esteem as a believer with a faith that is free from various diseases as an absolute condition for Islamic revival, enlightening the thinking (rationalizing) of Muslims in a moderate way. looking at cultural traditions and increasing the professional work ethic so that Muslims catch up until they are able to place the position of Islam and Muslims as noble and no one can match them.